Changing knowledge and perceptions of African indigenous vegetables: the role of community-based nutritional outreach. Issue 4 (19th May 2018) - Kansiime, Monica K.; Ochieng, Justus; Kessy, Radegunda; Karanja, Daniel; Romney, Dannie; Afari-Sefa, Victor
ABSTRACT: African indigenous vegetables (AIVs) have potential to sustainably address malnutrition, a growing problem in sub-Saharan Africa. Their consumption is however, limited by poor perceptions and lack of awareness of nutritional benefits. There is limited evidence of the effectiveness of community-focused information dissemination approaches in influencing participants' perceptions and uptake of innovations in AIVs to address malnutrition. This article aims to fill this knowledge gap, using a case study focusing on pastoral communities in Monduli district in northern Tanzania. Target communities participated in a community-based nutritional outreach facilitated by the Good Seed Initiative (GSI), held at Monduli district hospital in September 2014. The results provide evidence of the achievements of the GSI intervention, and the effectiveness of alternative information dissemination approaches.